A highly hydrophilic benzenesulfonic-grafted graphene oxide-based hybrid membrane for ethanol dehydration. Issue 34 (27th May 2020) - Tang, Lin; Lu, Yingying; Yao, Lulu; Cui, Peng
Abstract : A new type of hybrid membrane was prepared by blending sodium alginate with benzenesulfonic-grafted graphene oxide, which showed higher hydrophilicity and more defects or edges than GO to create channels for the transfer of water molecules. Abstract : A new type of hybrid membrane was prepared by blending sodium alginate (SA) with benzenesulfonic-grafted graphene oxide (BS@GO), which showed higher hydrophilicity and more defects or edges than GO to create channels for the transfer of water molecules. BS@GO was synthesized by reacting aryl diazonium salts with graphene oxide (GO). The BS@GO sheets were aligned parallelly to the membrane surface and affected the interactions between the SA chains. BS@GO could improve the hydrophilicity and pervaporation properties of SA-based hybrid membranes. Also, compared to GO fillers, BS@GO fillers could supply higher water permeance to improve the pervaporation flux and separation factor. For the pervaporation of 90 wt% aqueous ethanol at 343 K, the optimum hybrid membrane with 1.5 wt% BS@GO in the SA matrix showed the maximum permeate flux of 703 ± 89 g m −2 h −1 (1.4 times higher than that of an SA membrane), and the highest separation factor was 5480 ± 94 (5.6 times higher than that of the SA membrane). Moreover, the hybrid membrane exhibited good stability and separation ability during long-term testing.